Referencial curricular amazonense: a leitura e a formação de leitores em questão - Lobato, Ester Nogueira (Brasil, 2023)
This research, entitled “Referential Curricular Amazonense: The formation of reading of readers in question”, aims to identify the formative elements in the production of the subject reader in the 1st and 2nd years of Elementary School, in this way, an investigation was carried out in the field of reading present within the document Referencial Curricular Amazonense, which serves education in the state of Amazonas, emphasizing that this analysis will be carried out more particularly in the field that serves the initial years of fundamental education, with emphasis on the 1st and 2nd year. In addition, the listed objectives that served as rewards to give substance to this work were the following: to investigate the challenges to form the reader in the RCA perspective; analyze what the RCA says for the formation of the reader and understand how the RCA contemplates the intended skills in the field of action. When elaborating the research, we sought to answer and understand, through the problems, how the formation of readers happens, in order to observe and analyze the contributions of the document to guarantee education and the right in formation in view of the reader's perspective, since, the document contemplates education, culture and all the experiences of students, therefore, it is extremely resistant to investigation, in order to understand how this process of reading and literacy takes place within the school environment. In view of this, the methodological procedures examined in this work were qualitative research with an emphasis on descriptive document analysis research, whose first action, in addition to researching and understanding the document, was to survey the authors who discuss this topic. so interesting to be applicable. Through this, during the research it was possible to understand and observe in the data analysis what the authors and the document approach and finally reflect on the conversion of reader training to citizenship, in addition to exercising the right as critical and emancipated people.